The factors of involvement of bumiputera entrepreneurs in tourism sector in Bandar Hilir, Melaka / Muhammad Zulhelmi Anuar and Mohd Hafizan Salleh - Anuar, Muhammad Zulhelmi; Salleh, Mohd Hafizan (Faculty of Administrative Science and Policy Studies, 2013)
Tourism is one of the most important economic activities for any country. Every country has their Tourism sector activities. For Malaysia, tourism sector has developed actively and it has contributed to the economic growth. Melaka is one of States in Malaysia that extremely develop their Tourism sector. This Tourism sector has involved by many people from many ethnics such as Malays, Chinese and Indian. Hence, the study was done to identify the factors of involvement of Bumiputera Entrepreneurs in Tourism sector in Bandar Hilir, Melaka. Recommendations for the encouragement Bumiputera Entrepreneurs to involve Tourism sector are highlighted. There is also suggestion for the government. The factors of involvement of Bumiputera Entrepreneurs in Tourism sector in Bandar Hilir, Melaka are analysed. Data were collected from primary sources which are by distributing questionnaires. 65 questionnaires are distributed to respondents in Bandar Hilir area. Raw data on the variables were analysed by using SPSS application system (Statistical Package for Social Science). The finding shows a positive linear relationship between profit driven factor and the involvement of Bumiputera Entrepreneurs in Tourism sector in Bandar Hilir, Melaka. Other factors that have positive relationship with the involvement of Bumiputera Entrepreneurs in tourism Sector in Bandar Hilir, Melaka are standard of living and State Government encouragement.